KOMUNIKASI TOKOH MASYARAKAT RURAL DALAM MEMBANGUN DAERAHNYA PENGKAJIAN DI KECAMATAN GANTIWARNO, PRAMBANGAN, BAYAT, CAWAS, KABUPATEN KLATEN, JAWA TENGAH, 2007 - Gunadi, YS (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
The vallage is the represent home  stay somewhere permanently of the big society  as rural  districts.    They  are  do   on  the   tradisional   landscape   to  plantation   rises  or plantation another  plan  agricultures. There  are  manies  material  to  be  served   for economic people market  enough in their lives.  But, untl now  prosperity  group   of the  farmes  still upset indisonder   guided   information  leader.   Official Information Leaders of Agricultural of Subdistricts  (PPL) not yet rolling information  to the famers. Reason  its,  because  their himself  lessknowledge  and lesssciencies  about  agricultural system  like  the  coment  anather  farmers.  Its cosequences,  group   of the farmers  not  can run away  to the modernization technology agriculture. From it, the farmers still poor  misernstion in their life..